2020
DOI: 10.1177/0284185120980006
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography in diagnosing peritoneal metastases in ovarian carcinoma

Abstract: Multidetector computed tomography (MDCT) of the abdomen is currently the imaging examination of choice for the staging and follow-up of ovarian carcinoma (OC). Peritoneal metastases (PMs) represent the most common pathway for the metastatic spread of OC. MDCT scanners, due to several advantages—including increased volume coverage, reduced scanning time, acquisition of thin slices and creation of multiplanar reformations, and three-dimensional reconstructions—provide useful information regarding the early and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…undersurface of the left hemidiaphragm, spleen, pancreatic tail, and anterior and posterior surfaces of the stomach AR4 descending colon and left paracolic gutter AR5 pelvic side wall lateral to the sigmoid colon and sigmoid colon AR6 female internal genitalia with ovaries, tubes and uterus, urinary bladder, culde-sac of Douglas, and rectosigmoid colon AR7 right pelvic side wall and base of the cecum, including the appendix AR8 right paracolic gutter and ascending colon AR9-12 small bowel (AR9: upper jejunum; AR10: lower jejunum; AR11: upper ileum; and AR12: lower ileum) Imaging has a fundamental role in the accurate diagnosis of PMs in OC, helping to plan the appropriate therapeutic strategy, predict the likelihood of optimal cytoreduction, and identify potentially unresectable or difficult disease sites, which may require either IDS following chemotherapy or surgical technique modifications during PDS [3,[13][14][15][16][17][18][19][20][21][22].…”
Section: Ar3mentioning
confidence: 99%
See 1 more Smart Citation
“…undersurface of the left hemidiaphragm, spleen, pancreatic tail, and anterior and posterior surfaces of the stomach AR4 descending colon and left paracolic gutter AR5 pelvic side wall lateral to the sigmoid colon and sigmoid colon AR6 female internal genitalia with ovaries, tubes and uterus, urinary bladder, culde-sac of Douglas, and rectosigmoid colon AR7 right pelvic side wall and base of the cecum, including the appendix AR8 right paracolic gutter and ascending colon AR9-12 small bowel (AR9: upper jejunum; AR10: lower jejunum; AR11: upper ileum; and AR12: lower ileum) Imaging has a fundamental role in the accurate diagnosis of PMs in OC, helping to plan the appropriate therapeutic strategy, predict the likelihood of optimal cytoreduction, and identify potentially unresectable or difficult disease sites, which may require either IDS following chemotherapy or surgical technique modifications during PDS [3,[13][14][15][16][17][18][19][20][21][22].…”
Section: Ar3mentioning
confidence: 99%
“…Peritoneal metastases (PMs) represent the commonest pathway for the spread of OC and are often seen either at the time of initial diagnosis or at recurrence [3,[13][14][15][16][17][18][19][20][21][22]. The peritoneal cancer index (PCI) introduced by Jacquet and Sugarbaker combined the distribution of PMs in 13 abdominopelvic regions (ARs) with the tumor size providing a measurement of the volume of peritoneal carcinomatosis (PC) and also a valuable prognostic index (Table 1, Figure 1) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Different imaging techniques such as ultrasound [ 7 ], computed tomography (CT) [ 8 , 9 ], positron emission tomography/CT [ 10 ], and magnetic resonance imaging (MRI) [ 11 ] have been employed to detect peritoneal carcinomatosis from ovarian and gastrointestinal cancer [ 12 ]. In a recent published meta-analysis [ 13 ], the pooled sensitivity, specificity, and diagnostic odds ratio were reported to be as follows: 68%, 88%, and 15.9 for CT; 80%, 90%, and 36.5 for positron emission tomography/CT; and 92%, 85%, and 63.3 for diffusion-weighted MRI, respectively.…”
Section: Key Pointsmentioning
confidence: 99%
“…Ultrasound (US) is advantageous because of its accessibility as a first-line imaging examination that is painless and relatively inexpensive compared with computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET). Few studies have specifically compared the characteristics of metastatic ovarian malignancies of different origins (7)(8)(9)(10)(11)(12)(13). Such studies have reported that metastases in the ovaries are either predominantly or completely solid, but have failed to note specific sonographic features that characterize metastatic lesions.…”
Section: Introductionmentioning
confidence: 99%